Socio-Cultural Intelligence Perspective: Citizenship and National Defense in Indonesia's Plural Society - Kertopati, Susaningtyas Nefo Handayani (CV. Rayyan Dwi Bharata, 2025)
Indonesia is a country with a pluralistic society, consisting of various ethnicities, religions and other social groups. In various studies, pluralistic societies have socio-cultural threats in social conflict, insurgency/separatism and even disintegration. This is related to the activation of primordial sentiment as social solidarity in competition for limited resources, as well as structural problems such as injustice and inequality in development. This is in line with the shift in defense and security threats which do not only have a military dimension, but also non-military and hybrid ones. For this reason, a socio-cultural intelligence perspective is important in responding to the dynamics of this shifting threat. Because, as happened in Indonesia during the colonial period, post-New Order democratization, as well as more recently such as the Arab Spring phenomenon, as well as conflicts in northern Russia and Ukraine. So, the pluralism of society accompanied by structural problems is often exploited to create security instability in a country. The approach to citizenship and national defense through the Development of National Defense Awareness (PKBN) as a massive effort as a non-military defense strategy is important to maintain the diversity that exists in Indonesia. PKBN can build a strong Indonesian identity on top of a primordial identity to prevent politicization and exploitation which could lead to instability in Indonesia's security.